Development and Limited Test of Kinematics Conception Diagnostic Instrument: A Rasch Model Analysis Approach - Apriliana, Hana; Sasmita, Aden Yusril; Mustaqim, Ilham; Rahmawati, Rika; Suryana, Tresna Galih Sukma (CV. Dharma Samakta Edukhatulistiwa, 2025)
This study aims to identify and analyze misconceptions experienced by students on kinematics material. The approach used is quantitative, with a two-level diagnostic test method consisting of 10 multiple choice questions designed to detect misconceptions, involving 30 students of class XI MIPA at SMAN 4 Serang City. The research process included instrument development, expert validity test, limited trial, and data analysis. The question testing design used the Rasch Model Analysis method. Overall, this diagnostic test instrument showed good validity. The analysis results showed that the item reliability value reached 0.89, which indicated that the quality of the items was good. The findings of the data analysis show that students experience misconceptions caused by misunderstanding the concept of kinematics. Based on the results of this study, it is recommended that more effective learning strategies, such as the use of visual media and hands-on practicum, be applied to improve students' understanding of the concept of kinematics. In addition, training for teachers is also needed to improve their ability to identify and overcome misconceptions experienced by students.